“Simplicity is Key”: Literacy Graduate Students’ Perceptions of Online Learning - Van Wig, Ann; Yang, Shuling; Bahlmann Bollinger, Chelsey; Chen, Xiufang; Karkar Esperat, Tala; Pole, Kathryn; Wilson, Nance (Online Learning, 2022)
Even before COVID-19, literacy graduate coursework was increasingly offered online, replacing the traditional campus-based courses This study investigated how graduate literacy students perceive coursework in an online learning environment. This understanding is important because (a) student perceptions regarding online learning are critical to motivation and learning; and (b) faculty designing courses need to consider student voice in course development. This survey research queried literacy master’s degree candidates their perceptions prior to and after taking online classes, their confidence levels using technology, and about the technological tools that have impacted their learning. Results indicated initial perceptions of online learning changed positively after engagement in coursework, but course design influenced collaboration and engagement. Statistical significance was found in changes in initial perceptions of online learning to a more positive overall feelings toward online learning. The results of this study raise important considerations for implementing online coursework for literacy graduate students.